The Jobs That Youth Want and the Support They Need to Get Them: Evidence from a Discrete Choice Experiment in Kenya - Angela Elzir Assy; Tiago Ribeiro; David A. Robalino; Furio C. Rosati; Maria Laura Sanchez Puerta; Michael Weber (Institute of Labor Economics (IZA), 2019)
This paper presents the main results of three Discrete Choice Experiments designed to estimate youth preferences for different jobs attributes, and their willingness to pay for support services to access wage or self-employment. The experiments took place in urban areas in Kenya. We find that youth, in general, prefer to work in jobs that have the attributes of formal employment regardless of the tasks involved. Thus, they value earning stability, access to social insurance (in particular health insurance), and adequate working conditions. They do not have well defined preferences though between analytical vs. manual repetitive tasks or tasks that involve interpersonal/organizational skills or creativity. The main services youth demand to facilitate access to wage employment include jobs search assistance and training on soft-skills, followed by OJT and wage subsidies; they are not interested in technical training. For self-employment, they mainly seek support accessing credit, inputs and equipment, and insurance. Their willingness to pay for these services is modest relative to the average per capita cost of ALMPs, but it represents a substantial share of the payments made to youth and employers who participate in these programs.
Keywords: J2; J6; 330; youth employment; ALMP; discrete choice experiment